Improvement Of Nutritional Status Of Maternal Nutrition Through Local Available Foods. - Singh, Seema (International Journal of Psychosocial Rehabilitation, 2014)
Community-based approaches for improving nutrition, build capabilities and empower communities to effective demand services and at the same time support local available food for improving health and nutrition states of pregnant/lactating and children under two year. This involves increasing the participation of communities in the design, implementation and monitoring of research study and its interventions. Achieving household food and nutrition security requires coordination among local organizations that support food insecure groups.